2018
DOI: 10.2147/rsrr.s122301
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted vitreoretinal surgery: current perspectives

Abstract: Vitreoretinal microsurgery is among the most technically challenging of the minimally invasive surgical techniques. Exceptional precision is required to operate on micron scale targets presented by the retina while also maneuvering in a tightly constrained and fragile workspace. These challenges are compounded by inherent limitations of the unassisted human hand with regard to dexterity, tremor and precision in positioning instruments. The limited human ability to visually resolve targets on the single-digit m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 86 publications
0
25
0
Order By: Relevance
“…Evidence that surgeon tremor is a significant problem is a common justification for robot-assisted surgery ( Channa et al, 2017 ; Gudeloglu et al, 2014 ; Nuzzi & Brusasco, 2018 ; Riviere et al, 2006 ; Roizenblatt et al, 2018 ). Specifically, for one of the most technically demanding microsurgical fields, vitreoretinal surgery, a main technical limitation is imprecise maneuver during micromanipulation of tissues due to natural hand tremor ( Nuzzi & Brusasco, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that surgeon tremor is a significant problem is a common justification for robot-assisted surgery ( Channa et al, 2017 ; Gudeloglu et al, 2014 ; Nuzzi & Brusasco, 2018 ; Riviere et al, 2006 ; Roizenblatt et al, 2018 ). Specifically, for one of the most technically demanding microsurgical fields, vitreoretinal surgery, a main technical limitation is imprecise maneuver during micromanipulation of tissues due to natural hand tremor ( Nuzzi & Brusasco, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, for one of the most technically demanding microsurgical fields, vitreoretinal surgery, a main technical limitation is imprecise maneuver during micromanipulation of tissues due to natural hand tremor ( Nuzzi & Brusasco, 2018 ). In a recent review of robot-assisted vitreoretinal surgery, chief among the challenges faced by ultra-microsurgeons is physiologic hand tremor ( Roizenblatt et al, 2018 ). A high number of surgical procedures have been performed with robot assistance without enough evidence to support full implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Microscope-integrated OCT (MIOCT) may help prevent complications of inaccurate needle tip placement and repeat subretinal bleb formations such as hemorrhage, cannula tip obstruction, macular hole formation, retinoschisis, and RPE damage [ 43 ]. Robotic augmented vitreoretinal surgery has emerged in an effort to improve dexterity and control [ 44 ]. The first trial to use robotic-assisted surgery in human patients, the Robotic Retinal Dissection Device trial, demonstrated promising early safety results [ 45 ].…”
Section: Administration Routesmentioning
confidence: 99%
“…The robotic systems are effective for the purposes that require repetitive tasks, making the work easier for the ophthalmologist. [25]…”
Section: Potential Benefits Of Robotics In Ophthalmologymentioning
confidence: 99%